Two Cases of Primary Cold Agglutinin Disease Associated with Megaloblastic Anemia - Shinsaku Imashuku; Naoko Kudo; Katsushige Takagishi; Katsuyasu Saigo (Case Reports in Hematology)
We report two cases of primary cold agglutinin disease (CAD) associated with megaloblastic anemia in Japanese elderly patients. Case 1 was a 67-year-old male and Case 2 was a 55-year-old male. Both patients were diagnosed with primary CAD, with continuously high cold agglutinin titers (1 : >8,192 and 1 : 16,834, resp.), monoclonal IgM-kappa light chains, and no underlying disease. In addition, both patients had megaloblastic anemia due to vitamin B12 deficiency. One patient received rituximab and both received vitamin 12 supplementation. To date, no cooccurrence of primary CAD and megaloblastic anemia has been emphasized. Thus, the association of these hematological diseases may be incidental; however, given that CAD is an autoimmune disease which may show antibodies against intrinsic factor and gastric parietal cells, this association was thought to be probably not a coincidence. Clinicians should be aware of the possible simultaneous presence of autoimmune hemolytic/megaloblastic anemia in patients with primary CAD.